Photovoltaic Solar Energy Conversion - Bauer, Gottfried H. (Lecture Notes in Physics, 2015)
This concise primer on photovoltaic solar energy conversion invites readers to reflect on the conversion of solar light into energy at the most fundamental level and encourages newcomers to the field to help find meaningful answers on how photovoltaic solar energy conversion can work (better), eventually contributing to its ongoing advancement. The book is based on lectures given to graduate students in the Physics Department at the University of Oldenburg over the last two decades, yet also provides an easy-to-follow introduction for doctoral and postdoctoral students from related disciplines such as the materials sciences and electrical engineering. Inspired by classic textbooks in the field, it reflects the author's own ideas on how to understand, visualize and eventually teach the microscopic physical mechanisms and effects, while keeping the text as concise as possible so as to introduce interested readers to the field and balancing essential knowledge with open questions.